A novel screening tool to unmask potential interference between S‐ICD and left ventricular assist device. (14th October 2020) - Zormpas, Christos; Eiringhaus, Jörg; Hillmann, Henrike A. K.; Hohmann, Stephan; Müller‐Leisse, Johanna; Schmitto, Jan D.; Veltmann, Christian; Duncker, David
Abstract: Introduction: In patients with a left ventricular assist device (LVAD), the subcutaneous implantable cardioverter‐defibrillator (S‐ICD) can be an alternative to transvenous ICD systems due to reduced risk of systemic infection, which could lead to extraction of the ICD as well as the LVAD. S‐ICD eligibility is lower in patients with LVAD than in patients with end‐stage heart failure without LVAD. Several reports have shown inappropriate S‐ICD therapy in the coexistence of LVAD and S‐ICD. The aim of the present study was to evaluate S‐ICD eligibility in patients with LVAD using the established electrocardiogram (ECG)‐based screening test as well as a novel device‐based screening test to identify potentially inappropriate S‐ICD sensing in this specific patient cohort. Methods and Results: The present study included 115 patients implanted with an LVAD. The standard ECG‐based screening test and a novel device‐based screening test were performed in all patients. Eighty patients (70%) were eligible for S‐ICD therapy with the standard ECG‐based screening test. Performance of the novel device‐based screening test identified device‐device interference in 14 of these 80 patients (12%). Conclusion: Using a novel extended device‐based S‐ICD screening method, a small number of patients with LVAD deemed eligible for S‐ICD with the standard ECG‐based screening test exhibit device‐device interference. Careful S‐ICD screening should be performed in patients with LVAD, who are candidates for S‐ICD therapy, to prevent inappropriate sensing or ICD therapy.